PENGELOLAAN MUSEUM ARMA SEBAGAI DAYA TARIK WISATA BUDAYA DI DESA UBUD - I Nyoman Muliadi; Ida Ayu Suryasih (JURNAL DESTINASI PARIWISATA, 2016)
Arma Museum is a museum located in the village of Ubud. When viewed from the type collection Arma Museum categorized as museum of art. Arma Museum as a cultural tourist attraction, hopes to become a cultural center is a place for preserving art and culture, therefore the manager is expected to preserve the art of Balinese culture by means of training, education and organizing events related to art and culture of Bali. That assumption is underlying me to choose this topic for research. The topic is “Management of Arma Museum as Cultural Tourist Attraction in the village of Ubud”. The method used in this research is a research method with qualitative descriptive analysis technique to analyze management of Arma Museum . Sources of data derived from primary data and secondary data. Data collecting technique using in-depth interviews, observation and study of literature. Determination of informants from Arma Museum in this study using purposive sampling technique. This study is limited by using the concept of management, the concept of the museum, tourist attraction concept and the concept of cultural tourism. Five museums in the Ubud area has different types of categories the same collection are paintings, but in its management Arma Museum combines the museum as an institution which is a non-profit that is supported by the business unit such as a café, a coffee shop, Restaurant, and the cottages are located in the area Arma museum.. Arma Museum is able to become a cultural tourist attraction because apart from being institutions that preserve works of art, but the museum arma also able to preserve some kind of art such as dance, sculpture and traditional music.